Effect of flow path structure on solid/liquid separation under electric field - Tanaka, Takanori; Kato, Hiroki; Fujihara, Kenji; Jami, Mohammed Saedi; Iwata, Masashi (2014)
In this study, the factors determining the extent of electroosmotic pressure gradient (Epg) are discussed. Our theory of electroosmotic flow through porous materials predicts that the larger the specific hydrodynamic resistance,  of the material, the larger its Epg value. The empirical Epg values of various materials supports this prediction.